ALKS 4230: a novel engineered IL-2 fusion protein with an improved cellular selectivity profile for cancer immunotherapy. Issue 1 (21st April 2020) - Lopes, Jared E; Fisher, Jan L; Flick, Heather L; Wang, Chunhua; Sun, Lei; Ernstoff, Marc S; Alvarez, Juan C; Losey, Heather C
Abstract : Background: Interleukin-2 (IL-2) plays a pivotal role in immune homeostasis due to its ability to stimulate numerous lymphocyte subsets including natural killer (NK) cells, effector CD4 + and CD8 + T cells, and regulatory T cells (Tregs ). Low concentrations of IL-2 induce signaling through the high-affinity IL-2 receptor (IL-2R) comprised of IL-2Rα, IL-2Rβ, and common γ chain (γc ), preferentially expressed on Tregs . Higher concentrations of IL-2 are necessary to induce signaling through the intermediate-affinity IL-2R, composed of IL-2Rβ and γc, expressed on memory CD8 + T cells and NK cells. Recombinant human IL-2 (rhIL-2) is approved for treatment of metastatic melanoma and renal cell carcinoma (RCC), but adverse events including capillary leak syndrome, potentially mediated through interaction with the high-affinity IL-2R, limit its therapeutic use. Furthermore, antitumor efficacy of IL-2 may also be limited by preferential expansion of immunosuppressive Tregs . ALKS 4230 is an engineered fusion protein comprised of a circularly-permuted IL-2 with the extracellular domain of IL-2Rα, designed to selectively activate effector lymphocytes bearing the intermediate-affinity IL-2R. Results: ALKS 4230 was equipotent to rhIL-2 in activating human cells bearing the intermediate-affinity IL-2R, and less potent than rhIL-2 on cells bearing the high-affinity IL-2R. As observed in vitro with primary human cells from healthy donors and advanced cancer patients, ALKS 4230 induced greater activation and expansion of NK cells with reduced expansion of Tregs relative to rhIL-2. Similarly, in mice, ALKS 4230 treatment stimulated greater expansion of NK cells and memory-phenotype CD8 + T cells at doses that did not expand or activate Tregs . ALKS 4230 treatment induced significantly lower levels of proinflammatory cytokines, including tumor necrosis factor alpha, interleukin-6, and interferon gamma relative to rhIL-2. Furthermore, ALKS 4230 exhibited superior antitumor efficacy in the mouse B16F10 lung tumor model, where ALKS 4230 could be administered via multiple routes of administration and dosing schedules while achieving equivalent antitumor efficacy. Conclusions: ALKS 4230 exhibited enhanced pharmacokinetic and selective pharmacodynamic properties resulting in both improved antitumor efficacy and lower indices of toxicity relative to rhIL-2 in mice. These data highlight the potential of ALKS 4230 as a novel cancer immunotherapy, and as such, the molecule is being evaluated clinically.